Upaya Peningkatan Hasil Belajar PAI Kelas XI melalui Model Problem-Based Learning di SMK Negeri 1 Lintau Buo - Hakiki, Erisva (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
AThis study aims to determine the improvement of students’ learning outcomes in Islamic Religious Education (PAI) on the material of Evidence of Faith (Fulfilling Promises, Being Grateful for Blessings, Maintaining the Tongue, and Covering the Sins of Others) through the application of the Problem Based Learning (PBL) model. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The results show that in Cycle I, 44% of students achieved learning completeness, while in Cycle II, the completion rate increased to 75%. The application of PBL enhanced student activity and understanding of the material, although some students still did not meet the completion criteria. This study concludes that PBL is effective in improving students’ learning outcomes in PAI materia.